Nourishing care for early child development in Eastern Mediterranean region through early child nutrition: A case studies from six countries - Al-Jawaldeh, Ayoub; Abul-Fadl, Azza; Al-Jawaldeh, Fuad Eid (Indian Journal of Child Health, 2020)
Background: An optimum brain development requires a stimulating environment, adequate nutrients, and social interaction but is challenged by poverty and illiteracy. Aim: This study aims to assess the status of early child education (ECE) and child development (ECD) in relation to early feeding practices. Materials and Methods: The global data for ECE and ECD were obtained from the demographic health surveys. Breastfeeding practices, early intake of iron, and Vitamin A through foods versus supplements were studied in relation to ECE and ECD in the 31 provinces of six countries by socioeconomic status. ECE, stimulation, and care were studied for 16 countries in the region. Descriptive statistics and Pearson’s correlation were used for analysis with a cutoff of p<0.05. Results: Attendance in ECE and responsive care by father were highest in middle-income countries (28.4±19.25 and 45.125±25.4), early stimulation by responsive adult was highest in higher income (87±4.5), and learning materials at home and inadequate supervision at home were highest in lower-income countries. All domains of ECD correlated with attendance in ECE at p<0.01. Early stimulation and responsive care by adults were highly correlated with literacy and numeracy. There were significant correlations between exclusive breastfeeding for 6 months and attendance of ECE (p<0.05), early stimulation and responsive care by adults (p<0.01), and learning material (p<0.01). ECD domains were inversely associated with poverty and illiteracy. ECD index correlated significantly with the intake of iron and Vitamin A from fresh foods (p<0.05) but not from medicinal supplements (p>0.05). Conclusion: Early breastfeeding practices reinforce ECE which promotes ECD. Promoting early and continued breastfeeding is necessary for achieving nurturing care framework in developing countries.